2015
DOI: 10.1016/j.jcf.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is increased in cystic fibrosis and can skew the functional balance between ELR-positive and ELR-negative CXC-chemokines

Abstract: High expression of osteopontin is likely part of the dysregulated inflammation seen in CF, impairing the activities of ELR-negative chemokines that both serve as innate antibiotics and recruit NK and cytotoxic T cells, instead promoting an excessive influx of neutrophils, and may thus contribute to disease progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Osteopontin is a matricellular protein produced by macrophages that induces migration, proliferation, and adhesion of fibroblasts (31,32) and has been implicated in the pathogenesis of other fibrotic disorders (33)(34)(35)(36). Osteopontin has previously been implicated in human IPF (14).…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin is a matricellular protein produced by macrophages that induces migration, proliferation, and adhesion of fibroblasts (31,32) and has been implicated in the pathogenesis of other fibrotic disorders (33)(34)(35)(36). Osteopontin has previously been implicated in human IPF (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several cell surface‐expressed receptors for OPN have been identified including CD44, α9β4, α4β1, and α9β1, the latter, when expressed on neutrophils, resulting in chemotaxis . In a recent study, we found no binding of OPN to the neutrophil‐recruiting CXC chemokines GRO‐β/CXCL2, GCP‐2/CXCL6, or IL‐8/CXCL8 nor did it reduce the receptor‐activating properties of these chemokines . Furthermore, influx of neutrophils after OPN instillation was seen in noninflamed airways of mice and, in ozone‐induced lung injury, BALF neutrophils were significantly reduced in OPN deficient compared with wild‐type mice .…”
Section: Discussionmentioning
confidence: 56%
“…P . aeruginosa releases an elastase that generates a 60 amino acid peptide (VSS60) from full-length OPN ( Fig 4A ) [ 24 ]. To investigate whether this peptide retains properties that inhibit AMPs, viable counts was performed with P .…”
Section: Resultsmentioning
confidence: 99%